2017
DOI: 10.5152/ucd.2016.3190
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the publishing rate and the number of citations of general surgery dissertations

Abstract: Objective: A dissertation is a scientific document. However, if it is not published in a scientific journal, it will gain access to only a limited audience and thus will be unable to achieve its objective. Nevertheless, the rate of publishing in journals is not high among dissertations. In this study, we aimed to investigate the publishing rates of general surgery dissertations in journals and the total number of citations. Material and Methods:All medical dissertations that have been prepared at general surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 8 publications
1
19
0
3
Order By: Relevance
“…The study of Ozgen et al revealed that Turkish medical theses written between years 1980 and 2005 revealed that only 6.2% of the theses were published in MEDLINE indexed journals (6). A recent study of Mayir et al have also reported that the publication rate of the theses on general surgery in SCI/SCIE indexed journals is 22% (10). Relevant publications on general surgery in the literature have notified this ratio between 17% and 52% (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Ozgen et al revealed that Turkish medical theses written between years 1980 and 2005 revealed that only 6.2% of the theses were published in MEDLINE indexed journals (6). A recent study of Mayir et al have also reported that the publication rate of the theses on general surgery in SCI/SCIE indexed journals is 22% (10). Relevant publications on general surgery in the literature have notified this ratio between 17% and 52% (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…The presented research also reveals that experimental studies have significantly higher publishing rates. The reason of this difference is that clinical studies need more effort, take longer time to be finalized, longer length of follow-up facilitates the loss of patients, and experimental studies have more potential to provide original information which provides a higher potential for scientific publication (10). Although prospective randomized studies are the most valuable studies, these factors create a tendency on residents to compose experimental theses.…”
Section: Discussionmentioning
confidence: 99%
“…During the past decades, several studies investigated the publication rate of specialization in medicine theses in SCI-E journals in a variety of departments (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). In emergency medicine 14.9% of the theses between 1998 and 2013 (7); 22% of the theses in general surgery between 2006-2008 (9); 19.9% of the theses in gynecology and obstetrics between 2007-2008 (10); 10.7% of the theses in medical microbiology between 1997 and 2007 (11); 10.2% of the theses in clinical microbiology and infectious diseases between 1997 and 2007 (11); 18% of the theses in neurosurgery between 2004 and 2013 (12); 20.4% of the theses in ophthalmology between 1986 and 2010 (13); 12.5% of the theses in orthopedics and traumatology between 1974 and 2014 (15); and 32.7% of the theses in urology between 2008-2011 (17) were published in SCI/SCI-E journals.…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, several studies have investigated the publication rate of specialization in medicine theses in a variety of departments including emergency medicine (7), family medicine (8), general surgery (9), gynecology and obstetrics (10), medical microbiology (11), clinical microbiology and infectious diseases (11), neurosurgery (12), ophthalmology (13), otorhinolaryngology (14), orthopedics and traumatology (15), public health (16), and urology (17). However, no study has yet examined the publication rate of theses in medical ecology and hydroclimatology specialty.…”
Section: Introductionmentioning
confidence: 99%
“…Post-submission time to publication of journal articles is highly variable, with a wide range of 1 -7 years for Turkish general surgeon residents [11] and 16 -21 months for Thai paediatric residents. [12] Comparisons are difficult, because of novel reporting in the current study of presubmission publication, which does not feature in the perused literature.…”
Section: Researchmentioning
confidence: 99%